Penerapan Metode K-Means Dan Apriori Untuk Pemilihan Produk Bundling - Syifa Aryanti; Deni Mahdiana; Ade Setiadi (UNIVERSITAS RAHARJA, 2022)
The decision support system is very influential on the company's strategy in deciding a recommendation program that can overcome sales competition that changes according to trends every time and the impact of the Covid-19 pandemic has resulted in a drastic decline in sales and consumer attractiveness in the period January - March 2020, this is a a warning and a threat to the company that sales competition is getting bigger. PT. MSD is a distributor of kitchen utensils and middle-up fashion products from various well-known brands such as Jansport, Butterfly Twist, Thermos, Serena, Bodum, Arcoroc Luminarc and so on. Sales competition factors and the impact of the Covid-19 pandemic outbreak faced by PT. MSD triggers the company to prepare a new sales program with a product bundling strategy as an innovative promotion. The application of the K-Means and Apriori methods to the product bundling strategy was obtained from the results of Market Basket Analysis and sales data of PT. MSD to produce selected product recommendations that are clustered systematically and measurably so that PT. MSD can increase sales and consumer attractiveness with a choice of recommended products that consumers need.